Goodword Islamic studies grade 9 - Khanam, Farida (Goodword Books New Delhi [India], 2010)
This course has been designed to present the young students comprehensive Islamic education, comprising general Islamic knowledge based on the Quran and Hadith. Instead of teaching moral principles directly, they are taught through themes chosen from the Quran and other Islamic sources. A major portion of the course comprises the text of the Quran, which is followd by exercises to test the depth of understanding of the students. Though basically intended for use as a school text book, it is also an ideal tool for home schooling involving both the parents and the children. In this way children will not only learn the ethical values conveyed by the message of Islam but will also be stimulated to want to know more about Islamic teachings when they grow up.--Publisher description